Análise espacial e temporal de índices climáticos derivados das temperaturas máximas e mínimas para o Rio Grande do Sul - Costa, Cláudia Priscila Wanzeler da (2008)
Facing the possible global climate change already observed,this study aimed to identify the temporal trends of climate indices derived from the minimum and maximum temperatures for the Rio Grande do Sul.Daily data of minimum and maximum temperatures of 13 meteorological stations were used among 1961 and 2005.These data were organized in a seasonal way and later they were determined the climatic indexes.The indexes were defined for the seasonal averages,minimum absolute,maximum absolute,four percentílicas class (10%,35%,65%and 90%), waves of cold and of heat,for the maximum and minimum temperatures.They were appraised individually the significance (test t)of the coefficients of correlation of the indexes of the temperatures in the time.Finally,the values of t were contained in areas his/her homogeneous second significance.To generate the grouping the technique it was applied K means using as grouping criteria distances her quadratic. The results showed that the most significant variations happened in the minimum temperatures,which increased expressively in Extreme North,Northwest and Southeast of the State,possibly associate to the adding of steam of water in the atmosphere.The waves of cold of the minimum temperature increased in most of the State,while,the one of the maximum temperature reduced,except in the winter. Already the heat waves of the minimum and maximum temperatures increased significantly in Extreme North and Extreme East.Groupings of the values of the test t showed two groups with positive and significant variations formed by Iraí and Pelotas, and the other by Encruzilhada do Sul and Torres. Bom Jesus was only in the group with a range of significant reduction. The other meteorological station were classified as a group significant.